2020
DOI: 10.1111/jonm.12952
|View full text |Cite
|
Sign up to set email alerts
|

Differences in determinants of intention to stay and retention between younger and older nursing assistants in long‐term care facilities: A longitudinal perspective

Abstract: Aims This study examines differences in the determinants of intention to stay (Time 1) and actual retention behaviour at follow‐up (Time 2) between younger and older nursing assistants in long‐term care facilities. Background The shortage of nursing assistants in long‐term care is increasing, and the nursing assistant workforce is also ageing. Methods Data were obtained from a stratified equal probability sample of 595 nursing assistants from 137 institutions over a two‐year period in Taiwan. Multilevel modell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
(58 reference statements)
0
7
1
Order By: Relevance
“…In this study, the smoking cessation counselors' average score for intention to stay was 4.64 points (1–7 points). Studies have reported that the average willingness-to-stay scores of critical care nurses in intensive care units at urban hospitals, regular nurses employed in long-term care facilities, nursing assistants in nursing homes, and nursing assistants in long-term care facilities were 13.96 points (4–20 points), 3.5 points (1–5 points), 2.84 points (1–4 points), and 9.78 points (3–13 points), respectively, all of which are higher than our study population's average intention to stay ( 9 , 30 32 ). These studies were conducted in the context of a nursing shortage and heavy workload, and the intention to stay was still higher than that of this study.…”
Section: Discussioncontrasting
confidence: 65%
“…In this study, the smoking cessation counselors' average score for intention to stay was 4.64 points (1–7 points). Studies have reported that the average willingness-to-stay scores of critical care nurses in intensive care units at urban hospitals, regular nurses employed in long-term care facilities, nursing assistants in nursing homes, and nursing assistants in long-term care facilities were 13.96 points (4–20 points), 3.5 points (1–5 points), 2.84 points (1–4 points), and 9.78 points (3–13 points), respectively, all of which are higher than our study population's average intention to stay ( 9 , 30 32 ). These studies were conducted in the context of a nursing shortage and heavy workload, and the intention to stay was still higher than that of this study.…”
Section: Discussioncontrasting
confidence: 65%
“…This study found that the prevalence rate of turnover intention was high, which was consistent with Fang' study (Fang, 2016 ). Individual attributes such as young age, less years of nursing experience, a lower job title, unmarried status, contract employment (such as, staffing of personnel agent, contract employee), and lower pay were associated with novice nurses' high turnover intention (Chao & Lu, 2020 ; Yang & Chen, 2020 ), meanwhile, health administrators are advised to apply the job rotation approach by enhancing job satisfaction and reducing job conflict and turnover (Alfuqaha et al, 2021 ). Furthermore, the results indicated that workplace bullying was significantly correlated with turnover intention, and the indirect effect was mediated through psychological empowerment and job burnout.…”
Section: Discussionmentioning
confidence: 99%
“…The type of hospital, educational level, self‐evaluation, and professional status were found as important predictors of burnout (Alfuqaha et al, 2019 ). Previous studies found that younger nurses were more likely to face burnout (Chao & Lu, 2020 ) since they perceived that their profession lacked authority and power (Alfuqaha et al, 2019 ); moreover, 52.46% of novice nurses were reported as experiencing high levels of occupational burnout in China's public hospitals (Ma et al, 2021 ). Liu et al ( 2018 ) demonstrated that workplace violence had a positively significant relationship with job burnout and turnover intention for Chinese nurses in a tertiary hospital.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study of nurses' actual turnover and personal characteristics found increased likelihood of being single, aged 30 or younger, and ≤3 years of hospital working experience (Dewanto & Wardhani, 2018). Chao and Lu (2020) found that intention to stay was related to actual retention 2 years later; other predictive factors were married, optimization and low emotional exhaustion. A meta-analysis (Nei et al, 2015) of voluntary turnover found that nurses who had worked at the organisation for a longer period, were older and had higher network centrality, higher job control, perceived good leadership (supportive and communicative), higher commitment, job involvement and job satisfaction were less likely to leave.…”
Section: Introductionmentioning
confidence: 99%